Comparison of tribological performance of zinc dialkyldithiophosphate (ZDDP) in poly-alpha-olefin (PAO) and palm oil-based trimethylopropane (TMP) ester - Zahid, Rehan; Hassan, Masjuki; Munusamy, Mahendra Varman; Mufti, Riaz Ahmad; Kalam, Md. Abul; Gulzar, Mubashir; Yunus, Robiah (Malaysian Tribology Society, 2015)
Due to environmental legislations, automotive industry is striving hard to shift from mineral/synthetic oils to environmental friendly ones such as vegetable oils. In this study, effectiveness of ZDDP in enhancing the tribological properties of steel/steel contact, when used in combination with palm-oil based TMP ester, has been investigated and the results are compared with that of PAO. Friction and wear experiments were carried out using four-ball tribo-testing machine. TMP and TMP+PAO offered low values of friction compared to PAO. In addition, ZDDP-derived tribofilm was detected on the interacting surfaces, when TMP+PAO+ZDDP lubricant was used, resulting in decreased wear.